2020
DOI: 10.2139/ssrn.3520421
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Administration in Fledgling Democracies: Experimental Evidence from Kenya

Abstract: We examine the effects of national voter registration policies on voting patterns with a large-scale experimental study. Together with Kenya's electoral commission, we designed an experiment in which 1,674 communities were randomized to a status quo or treatment group, receiving civic education on voter registration, SMS reminders about registration opportunities, and/or local registration visits by election commission staff. We find little evidence that civic education improves registration. Local registratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 35 publications
0
14
2
Order By: Relevance
“…Our study contributes sorely needed descriptive facts to a nascent literature exploring voter registration status, rather than turnout, in lower-income countries (Harris et al, 2021; Ichino & Schündeln, 2012; Mvukiyehe & Samii, 2017). It also complements a growing body of work examining the role of relational attributes in explaining political behavior.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our study contributes sorely needed descriptive facts to a nascent literature exploring voter registration status, rather than turnout, in lower-income countries (Harris et al, 2021; Ichino & Schündeln, 2012; Mvukiyehe & Samii, 2017). It also complements a growing body of work examining the role of relational attributes in explaining political behavior.…”
Section: Introductionmentioning
confidence: 93%
“…Turning to the context of lower-income countries, Harris et al (2021) found that an intervention reducing the cost of registration in Kenya—conducting mobile registration rather than requiring citizens to register in-person—increased registration, particularly in poorer communities. However, this analysis was conducted at the aggregate rather than individual level.…”
Section: Determinants Of Registration: Theory and Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Younger citizens (y-axis) have lower turnout rates compared to older citizens (x-axis), especially so in non-democracies (right panel). This figure reports survey estimates of youth (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and adult (35+) turnout from the most recent election for which sufficiently high-quality data is available. Democracies are those countries that have a Polity-V score above 5.…”
mentioning
confidence: 99%
“…This, we suspect, might be because the implementation of the registration treatment was somewhat convoluted. Indeed, unlike some past studies (e.g., 19), we were not allowed to interface directly with the state's voter registration system.…”
mentioning
confidence: 99%